2020
DOI: 10.1097/md.0000000000023133
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant brain-expressed X-linked 4 (BEX4) expression is a novel prognostic biomarker in gastric cancer

Abstract: Background: This study aimed to investigate the expression level of X-linked 4 (BEX4) in patients with gastric cancer (GC) and to investigate the prognostic significance of BEX4. Methods: The mRNA expression of BEX4 was analyzed using the Cancer Genome Atlas (TCGA) datasets. The relationship between the expression of BEX4 and GC patient survival was assessed using a Kaplan-Meier plot and Log Rank test. Multivariate cox regression analysis was used to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(20 reference statements)
1
2
0
Order By: Relevance
“…Many studies have reported that the abnormal expression of BEX family genes was related to the development and prognosis of tumors, such as GBM, gastric cancer, colorectal cancer, hepatocellular carcinoma, lung cancer, and breast cancer (11,(25)(26)(27)(28). Here, through the analysis of GBM samples in TCGA database, we once again verify that, except for BEX3, BEX family genes were significantly downregulated in GBM.…”
Section: Aberrant Expression Of Bex Family Genes In Glioblastoma Mult...supporting
confidence: 62%
See 1 more Smart Citation
“…Many studies have reported that the abnormal expression of BEX family genes was related to the development and prognosis of tumors, such as GBM, gastric cancer, colorectal cancer, hepatocellular carcinoma, lung cancer, and breast cancer (11,(25)(26)(27)(28). Here, through the analysis of GBM samples in TCGA database, we once again verify that, except for BEX3, BEX family genes were significantly downregulated in GBM.…”
Section: Aberrant Expression Of Bex Family Genes In Glioblastoma Mult...supporting
confidence: 62%
“…Members of the BEX family have also reported a prognostic correlation in other tumors, such as gastric cancer and liver cancer ( 27 , 29 ). In our study, it can also be found that the downregulation of the BEX genes was correlated with the worse prognosis (except for BEX5).…”
Section: Discussionmentioning
confidence: 99%
“…24 BEX family proteins are known to play a role in neuronal development and recent studies suggest a role in cancers. [25][26][27][28][29] BEX1 suppressed tumor cell growth of esophageal squamous cell cancer, colorectal cancer, acute myeloid leukemia, oral squamous cell carcinoma, malignant glioma. [30][31][32][33][34] But in lung adenocarcinoma, malignant pleural mesothelioma and GBM, BEX1 promoted tumor cell growth.…”
Section: Discussionmentioning
confidence: 99%